PHYOX2: a pivotal randomized study of nedosiran in primary hyperoxaluria type 1 or 2 - Baum, Michelle A.; Langman, Craig; Cochat, Pierre; Lieske, John C.; Moochhala, Shabbir H.; Hamamoto, Shuzo; Satoh, Hiroyuki; Mourani, Chebl; Ariceta, Gema; Torres, Armando; Wolley, Martin; Belostotsky, Vladimir; et al. (Kidney international, 2023)
Nedosiran is an investigational RNA interference agent designed to inhibit expression of hepatic lactate dehydrogenase, the enzyme thought responsible for the terminal step of oxalate synthesis. Oxalate overproduction is the hallmark of all genetic subtypes of primary hyperoxaluria (PH). In this double-blind, placebo-controlled study, we randomly assigned (2:1) 35 participants with PH1 (n = 29) or PH2 (n = 6) with eGFR ≥30 mL/min/1.73 m2 to subcutaneous nedosiran or placebo once monthly for 6 months. The area under the curve (AUC) of percent reduction from baseline in 24-hour urinary oxalate (Uox) excretion (primary endpoint), between day 90-180, was significantly greater with nedosiran vs placebo (least squares mean [SE], +3507 [788] vs −1664 [1190], respectively; difference, 5172; 95% CI 2929-7414; P < 0.001). A greater proportion of participants receiving nedosiran vs placebo achieved normal or near-normal (<0.60 mmol/24 hours; <1.3 × ULN) Uox excretion on ≥2 consecutive visits starting at day 90 (50% vs 0; P = 0.002); this effect was mirrored in the nedosiran-treated PH1 subgroup (64.7% vs 0; P < 0.001). The PH1 subgroup maintained a sustained Uox reduction while on nedosiran, whereas no consistent effect was seen in the PH2 subgroup. Nedosiran-treated participants with PH1 also showed a significant reduction in plasma oxalate versus placebo (P = 0.017). Nedosiran was generally safe and well tolerated. In the nedosiran arm, the incidence of injection-site reactions was 9% (all mild and self-limiting). In conclusion, participants with PH1 receiving nedosiran had clinically meaningful reductions in Uox, the mediator of kidney damage in PH.